Internet dan Kebahagiaan di Masa Pandemi - Aidal Masrura; Ratna Djuwita; Joevarian Hudiyana (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
This study aims to see the relationship between internet use and happiness, especially during the pandemic Covid-19. This study uses a non-experimental quantitative approach utilizing bivariate correlation analysis. There were 3938 respondents consisting 76% women in this study. The results showed that internet use, in general, was correlated with happiness, but not across all dimensions of internet use. Dimensions that are positively and significantly correlated are only those dimensions that can meet basic psychological needs. The implications of this research need to be discussed further.